Cervical spine clearance in adults following blunt trauma: a national survey across major trauma centres in England. Issue 4 (April 2018) - Chilvers, G.; Porter, K.; Choudhary, S.
Abstract : Aim: To assess current practice in cervical spine clearance across major trauma centres in England and review current guidelines. Materials and methods: An electronic survey was sent to lead trauma clinicians at 22 major trauma centres in England. This assessed the clinical decision tools used, the choice of initial imaging technique, and the methods used to clear the cervical spine in alert and obtunded patients without focal neurology, and where initial imaging was normal. British Orthopaedic Association Standards for Trauma (BOAST) 2 and Eastern Association for Surgery for Trauma (EAST) guidelines were used as standards. Results: Eighteen out of the 22 (82%) centres responded by completing the survey. Most (71%) centres used the Canadian C-Spine Rule for clearing the cervical spine clinically. Seventy-two percent of centres preferred computed tomography (CT) as the first-line imaging technique, the choice based on age of patient and mechanism of injury. If the initial CT imaging was normal, magnetic resonance imaging (MRI) was performed in 52% of centres to clear the cervical spine, with half of these centres stating that they would discuss further imaging with a radiologist first. The practice across centres was highly variable for the obtunded patient, with most centres preferring continuing immobilisation or MRI to clear the cervical spine, with a small minority removing spinal precautions when a high-quality multidetector CT was normal. Conclusion: Multidetector CT is the preferred initial imaging technique across most major trauma centres in England when blunt cervical spine trauma is suspected. There is widespread reliance on MRI to clear the cervical spine in both alert and obtunded patients, if initial CT imaging is normal and there is no focal neurology on clinical assessment. This calls for greater awareness of the reliability of a high-quality normal multidetector CT examination in clearing the cervical spine in the absence of focal neurology. Highlights: Observational study to assess cervical spine clearance protocols in adults across major trauma centres. Multidetector CT scan is the preferred initial imaging modality for assessing blunt cervical spine injury in adults. There is widespread reliance on MRI to clear the cervical spine in both alert and obtunded patients. Greater awareness of the reliability of a high quality normal MDCT examination in clearing the cervical spine is required.